Irrigation System Implementation Implications of Renewable Subak Land on Rice Field in Bali - Dewi Yuliana, Euis; Wayan Watra, I; Sitepu, Israil; Wulaning Ayu, Putu Desiana; Angga Pradipta, Gede (Opción, 2019)
Subak as an organization of traditional irrigation system in Bali, at this time because there is a tendency to be concerned about its sustainability has declined. There are several factors, one of which is decreasing the quantity and quality of irrigation water. At first the farmers of Subak members never questioned the state of irrigation water because its use has not been so com- plex and the numbers are still plentiful. Along with the resulting develop- ment of irrigation water for agricultural purposes the number is increasing slightly. In this regard, the need to restructure Subak irrigation system in irrigate (rice), without having implications for the reduction of rice produc- tion per unit area. This study focuses to address the problems outlined in the following three questions. 1) How implications of the application of renewable irrigation system on rice production. 2) How implications renewable irrigation system implementation to environment. 3) How impli- cations of the application on renewable irrigation system in social environ- ment among farmers? From this research can be summarized as follows. First, the application of renewable irrigation system (irrigation system is disconnected / intermittent irrigation) on both of subak in Bali, Subak of Gunung Sari subak on Jatiluwih village and Wangaya Betan Subak on Mengesta village, have significant implications for the increased production of wet rice, nearly twice folding of 4-5 tons a hectare to 7-8 tons a hectare. Also the implementation of this renewable irrigation system (irrigation system is disconnected / intermittent irrigation) are cost of production, if labor and time farmers in the value of money. Second, the adoption of irriga- tion systems interrupted (intermittent irrigation) both at Wangaya Betan Subak and Gunungsari Subak evidently has implications for improving the condition of the land, improvements ecosystems fields, and the environment in general Third, the implementation of irrigation systems interrupted (intermittent irrigation) both in Subak Wangaya Betan and in Subak Gunungsari was able to suppress of conflict in competition for water utiliza- tion, so that the social environment in the community can be conducive.